Konflik Sosial dalam Novel Corona Karya Sdavincii - Nugroho, Rafli Adi; Mubharok, Anwar; Ramadhani, Nur Fadhilah Rizqi (Kajian Bahasa dan Sastra (KABASTRA), 2024)
This research aims to describe the social conflict contained in the novel Corona by Sdavincii. The method used to collect data is the literature study method. Then, to analyze the data, a qualitative descriptive method was used which was carried out by taking problems or focusing on problems as they were when the research was carried out. The results of this research show that the conflicts contained in the Corona novel are political conspiracy issues, health conflicts about Corona, economic conflicts about economic differences between Aragon and Catalan, moral conflicts about good moral issues, family conflicts about the Lago family and the Ella family.